Maqâshid al-Syarî`ah al-Shâthibî and Ibn `Ashûr’s Perspectives on al-Qitâl Verse - Bin Mujib, Lalu Supriadi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2021)
The verse of al-Qitâl is frequently exploited as a symbol to instill a negative stigma against Islam and trigger the emergence of religious radicalism, which disrupts Muslim-non-Muslim relations. This study aims to look into al-Shâthibî and Ibn `Ashûr's perspectives of Maqâshid al-Syarî`ah and its relation to the verse of al-Qitâl. Studies revealed that al-Shâthibî and Ibn `Ashûr had the same passion for Islamic law reform. Differences arise in the methodological and conceptual domain employed to identify and map Maqâshid al-Syarî`ah. Al-Shâthibî uses it to refer to the Maqâshid al-Syarî`ah trilogy, which includes the purpose of Islamic law discourse, Islamic law philosophy, and Islamic law principle. On the other hand, al-Shâthibî only provides examples of application related to the goals of Islamic law discourse. Meanwhile, Ibn `Ashûr limits its application to the purpose of Islamic law philosophy related to morals and ethics. Furthermore, al-Shâthibî identify the dimensions of Hifz al-Dîn (protection of religion) in the verse of al-Qitâl using the istiqrâ’ (induction), which is an Islamic law discourse methodology, while Ibn `Ashûr identify them based on the philosophy of Islamic law. This study concludes that al-Shâthibî and Ibn `Ashûr’s perspectives of the verse of al-Qitâl contain Maqâshid al-Syarî`ah content. Ayat al-Qitâl sering dimanfaatkan sebagai simbol untuk menanamkan stigma negatif terhadap Islam dan memicu munculnya radikalisme agama, yang mengganggu hubungan Muslim-non-Muslim. Penelitian ini bertujuan untuk melihat perspektif al-Shâthibî dan Ibn `Ashûr tentang Maqâshid al-Syarî`ah dan kaitannya dengan ayat al-Qitâl. Studi mengungkapkan bahwa al-Shâthibî dan Ibn `Ashûr memiliki semangat yang sama untuk reformasi hukum Islam. Perbedaan muncul dalam ranah metodologis dan konseptual yang digunakan untuk mengidentifikasi dan memetakan Maqâshid al-Syarî`ah. Al-Shâthibî menggunakannya untuk merujuk pada trilogi Maqâshid al-Syarî`ah yang meliputi tujuan wacana hukum Islam, filsafat hukum Islam, dan prinsip hukum Islam. Di sisi lain, al-Shâthibî hanya memberikan contoh penerapan yang terkait dengan tujuan wacana hukum Islam. Sementara itu, Ibn `Ashûr membatasi penerapannya pada tujuan filsafat hukum Islam yang berkaitan dengan moral dan etika. Selanjutnya, al-Shâthibî mengidentifikasi dimensi Hifz al-Dîn (perlindungan agama) dalam ayat al-Qitâl menggunakan istiqrâ’ (induksi), yang merupakan metodologi wacana hukum Islam, sedangkan Ibn `Ashûr mengidentifikasinya berdasarkan filsafat hukum Islam. Penelitian ini menyimpulkan bahwa perspektif al-Shâthibî dan Ibn `Ashûr terhadap ayat al-Qitâl mengandung muatan Maqâshid al-Syarî`ah.